Family medical care Volume 4: marvels of the human frame - Knight, John F. (Signs Publishing Company , Warburton, Vic., 1990)
Volume 4 of Family Medical Care (five volumes) is an integral part of the series. Its various sections offer a striking introduction to anatomy, while various chapters unravel the mysteries of the body's systems, how they work, what goes wrong and how they are managed. Includes information on
"A five-volume illustrated series covering all aspects of health care, incorporating the assistance of more than 50 medical and paramedical specialists." Dr James Wright is the pen-name used by Dr John F. Knight. This name is also used on a cover of one of the volumes
Keywords: Diseases